Método objetivo para evaluar la agudeza visual dinámica utilizando respuestas pupilares - Zúñiga López, A.; Suaste Gómez, E. (Revista Mexicana de Ingenieria Biomedica, 2002)
The purpose of this work is to evaluate objectively the visual acuity (VA), using optotypes in movement, of a subject with optic correction and without it making use of its pupillary response. To measure the VA, the conditions of luminance and contrast are settled down. Once the conditions of the study are controlled, an optotype in movement is introduced to the subject. The sinusoidal frequency of the optotype is varied starting from 0.1 Hz and gradually increasing, until the subject is not able to distinguish the character of the Snellen chart. The objective VA is obtained using the technique of video-oculography which can detect the pupillary changes by means of images processing. The results obtained by this method, that is, when reflex dilatation of the pupil coincides with the moment in which the subject stops to perceive the optotype, guarantees that this method can be considered as an objective for the evaluation of the VA dynamics. In the same way, the results demonstrate that the visual system of an individual to detect, to recognize or to solve details of an image is different if the object or the image is in motion.